Erratum: Andrew T. McDonald, Eduardo Espílez, Luis Mampel, James I. Kirkland & Luis Alcalá (2012) An unusual new basal iguanodont (Dinosauria: Ornithopoda) from the Lower Cretaceous of Teruel, Spain. Zootaxa, 3595, 61–76. - Mcdonald, Andrew T.; Espílez, Eduardo; Mampel, Luis; Kirkland, James I.; Alcalá, Luis (Zootaxa, 2013)
(Erratum)